Modern solution for dual-purpose protective structures (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is devoted to the identification of a modern solution for dual-purpose protective structures, which provides the possibility of reusing sections of protective structures. The main feature is the ability to perform not only a protective function, but also to be used in peacetime as public, commercial or transport facilities. This approach allows for the effective integration of such structures into the urban environment, reducing the burden on the budget and optimizing the use of space.The design of protective structures requires taking into account a number of specific conditions, in particular, increased requirements for the strength of structures, ensuring tightness, autonomy and an effective ventilation system. An important aspect is the ability of such structures to quickly transform into a shelter mode, guaranteeing reliable protection from external threats. The introduction of modern materials, in particular high-strength concrete, steel frames and composite elements, allows for increasing the durability and stability of structures. Ergonomics plays a key role in ensuring the comfortable stay of people for a long time. Optimization of spatial planning involves the creation of convenient recreation areas, medical facilities, sanitation systems and any other premises for comfortable use of the space of the protective structure. Also, taking into account the needs of people with disabilities, which is achieved through a barrier-free environment, adaptive design of sections of the protective structure and ergonomic spaces.Modern trends in the design of dual-purpose protective structures are aimed at integrating energy-efficient technologies, automated life support systems and modular structures, which allows you to quickly adapt structures to different usage scenarios. This not only increases the level of safety, but also makes such structures part of sustainable urban development, which is necessary for modern challenges and needs of society.
Keywords: protective structures; dual-purpose; modular structures; concrete; adaptation; usage scenarios